Adhesion and metabolic activity of human corneal cells on PCL based nanofiber matrices - Stafiej, Piotr; Küng, Florian; Thieme, Daniel; Czugala, Marta; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Advances in Materials Science and Engineering, 2017)

Adhesion and metabolic activity of human corneal cells on PCL based nanofiber matrices. - Stafiej, Piotr; Küng, Florian; Thieme, Daniel; Czugala, Marta; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Materials Science and Engineering C, 2017)
In this work, polycaprolactone (PCL) was used as a basic polymer for electrospinning of random and aligned nanofiber matrices. Our aim was to develop a biocompatible substrate for ophthalmological application to improve wound closure in defects of the cornea as replacement for human amniotic membrane. We investigated whether blending the hydrophobic PCL with poly (glycerol sebacate) (PGS) or chitosan (CHI) improves the biocompatibility of the matrices for cell expansion. Human corneal epithelial cells (HCEp) and human corneal keratocytes (HCK) were used for in vitro biocompatibility studies. After optimization of the electrospinning parameters for all blends, scanning electron microscopy (SEM), attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), and water contact angle were used to characterize the different matrices. Fluorescence staining of the F-actin cytoskeleton of the cells was performed to analyze the adherence of the cells to the different matrices. Metabolic activity of the cells was measured by cell counting kit-8 (CCK-8) for 20days to compare the biocompatibility of the materials. Our results show the feasibility of producing uniform nanofiber matrices with and without orientation for the used blends. All materials support adherence and proliferation of human corneal cell lines with oriented growth on aligned matrices. Although hydrophobicity of the materials was lowered by blending PCL, no increase in biocompatibility or proliferation, as was expected, could be measured. All tested matrices supported the expansion of human corneal cells, confirming their potential as substrates for biomedical applications.

A novel suture retention test for scaffold strength characterization in ophthalmology. - Küng, Florian; Schubert, Dirk W.; Stafiej, Piotr; Kruse, Friedrich; Fuchsluger, Thomas (Materials Science and Engineering C, 2016)
Sutures are a common way to attach scaffolds in patients. For tubular cardiac scaffolds, the 'suture retention strength' is commonly used to evaluate the resistance of a scaffold against the pull-out of a suture. In order to make this quantity accessible for ophthalmological scaffolds the test procedure has been modified in a novel way. Polycaprolactone (PCL) films of different thicknesses and an amniotic membrane (AM) were used for the experiments. Circular samples with a radius of 7mm were taken and a suture was passed through each sample and tied to a loop. The sample was clamped in a tensile tester and a bolt was passed through the loop. The suture was then pulled with a constant deformation rate until pull-out occurred. The suture retention strength, the deformation at the suture retention strength, and the deformation at rupture were determined for each sample. The presented modified suture retention test allows to measure the relevant parameters of samples on the scale of ophthalmological scaffolds in a reproducible way. A comparison between the first data on PCL and AM has been made.

Designing novel scaffolds for ocular surface reconstruction based on aligned nanofibers - Küng, Florian; Fuchsluger, Thomas; Schubert, Dirk W. (Polychar, 2017)

Identification of Process Limits for Electro-Spinning of aligned – Nano Fibres of the CPL/PGS 1: 1 blend - Bischoff, S.; Küng, Florian; Stafiej, Piotr; Fuchsluger, Thomas; Boccaccini, Aldo R.; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

Influence of operating parameters on the suture retention test for scaffolds in ophthalmology - Küng, Florian; Schubert, Dirk W.; Stafiej, Piotr; Kruse, Friedrich; Fuchsluger, Thomas (Materials Science and Engineering C, 2017)
The strength of a suture used to attach a graft to a patient can be quantified using the suture retention test. In order to gain deeper insight on the influence of testing and application conditions testing parameters were varied. Different pull rates, suture and jaw positions, and suture materials were tested to show their influence on the result of the test. The results of the different states were analyzed using statistical tests. Based on the statistic analysis conditions for testing with a maximum of accuracy and as close as possible to in vivo conditions have been revealed.
EVALuna2:21344

Influence of the molar mass distribution on the suture-ability of nanofiber meshes for tissue engineering - Hehn, Markus; Küng, Florian; Stafiej, Piotr; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (15th Bayreuth Polymer Symposium, 2017)

Influence of the molar mass on the suture retention properties of polycaprolactone - Küng, Florian; Schubert, Dirk W. (Europe Africa Conference 2017 of the Polymer Processing Society, 2017)

Influence of the molecular weight on the suture retention properties of polycaprolactone - Küng, Florian; Schubert, Dirk W.; Stafiej, Piotr; Kruse, Friedrich; Fuchsluger, Thomas (Association for Research in Vision and Ophthalmology, 2017)

Mapping of the electrospinning parameters for PLGA-Nanofibers - Regelmann, Christian; Küng, Florian; Stafiej, Piotr; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (15th Bayreuth Polymer Symposium, 2017)

One-Dimensional Relaxation and Compression Behaviour Hydrogels as Inhomogeneous Bulk Material - Küng, Florian; Schubert, Dirk W. (14th Bayreuth Polymer Symposium, 2015)

One-Dimensional Relaxation Behaviour and Compression of Superabsorbent Polymers as Inhomogeneous Bulk Material - a Novel Approach to reveal corresponding consecutive Differential equation - Küng, Florian; Schubert, Dirk W. (European Polymer Federation, 2015)

One-Dimensional Relaxation Behaviour and Compression of Superabsorbent Polymers as Inhomogeneous Bulk Material - a Novel Approach to reveal corresponding consecutive Differential equation - Schubert, Dirk W.; Küng, Florian (10th Annual European Rheology Conference, 2015)

Shear rheology of nanofiber reinforced alginate solutions for bioprinting - Schrüfer, Stefan; Küng, Florian; Schubert, Dirk W. (Deutsche Gesellschaft für Biomaterialien - Annual Meeting, 2018)
Keywords: shear rheology; nanofiber; bioprinting

Suture-ability of patch grafts for ocular surface reconstruction - Küng, Florian; Fuchsluger, Thomas; Schubert, Dirk W. (Polychar, 2017)

Suture retension test method for opthalmological materials - Voigt, Monika; Thieme, Daniel; Küng, Florian; Schubert, Dirk W.; Kruse, Friedrich; Fuchsluger, Thomas (Deutsche Gesellschaft für Biomaterialien, 2018)
Keywords: biomaterialien; espinning suture retension

Transparency of nanofiber reinforced alginate hydrogels for corneal wound healing - Stafiej, Piotr; Küng, Florian; Kruse, Friedrich; Schubert, Dirk W.; Fuchsluger, Thomas (Association for Research in Vision and Ophthalmology, 2017)

Transparency of suture able polycaprolactone nanofiber hydrogel compounds (NFHC) for medical application in ophthalmology - Stafiej, Piotr; Küng, Florian; Fuchsluger, Thomas; Schubert, Dirk W. (Deutsche Gesellschaft für Biomaterialien 2017, 2017)